Comparison of calibration methods in the analysis of 2013 Brazilian National Health Survey data - Juliana Sena de Souza; Márcia Helena Barbian; Rodrigo Citton Padilha dos Reis (Revista Brasileira de Epidemiologia)
ABSTRACT Objective: This study aims to compare calibration methods for weights in the subsample of Laboratory Exams from the 2013 Brazilian National Health Survey (PNS), seeking to assess their representativeness and precision. Methods: Two alternative proposals for constructing calibrated weights were performed based on post-stratification and raking methods. A comparison between the weights provided for the Laboratory Exams subsample and the two suggested weights was conducted through parameter estimates using the 2013 PNS subsample data. Additionally, seven measures were used to assess the performance of the proposed weighting systems. Results: The alternative post-stratification and raking weights produced generalizable estimates for the target population of the 2013 PNS, while the original weights did not. The alternative methods showed similar performance to the original method, with a slight advantage for raking in some evaluation measures. Conclusion: It is recommended that basic design weights be documented and included in the public-use data files of the PNS. Furthermore, it is suggested to cross-reference information between the sample and subsample of the 2013 PNS to enable the exploration of methods such as data imputation, aiming to obtain more accurate and representative estimates. These improvements are essential to ensure the quality and usefulness of PNS data in epidemiological and public health studies.